(untitled) (REMUNOM, 2025)
Introduction: The upper canine is an essential tooth for aesthetics and occlusal function and is commonly associated with cases of dental impaction due to pathologies associated with cysts or tumors, changes in the path and chronological order of eruption. Treatment consists of orthodontic traction to perform adequate movement to the occlusion line; however, in complex cases such as dental ankylosis or resorption of adjacent teeth, extraction is necessary. Objective: to report a clinical case of extraction of an included canine in the maxillary region. Case Report: A 14-year-old female patient, non-smoker, leucoderma and without systemic alterations, was referred to the UFCG School of Dentistry Clinic, Patos-Paraíba, with the main complaint of an included and impacted upper canine. After clinical and radiographic diagnosis, extraction planning was performed, in which the following steps were followed: anesthesia, incision, mucoperiosteal flap and tissue divulsion, followed by luxation of the included and impacted tooth with the aid of straight and curved levers. After tooth removal, the flap was positioned and scalloped sutures were performed. Rest and pain control with analgesics and anti-inflammatories were indicated as postoperative measures. Conclusion: Early diagnosis of impacted teeth is necessary for correct planning of the case and should be performed through clinical and radiographic examination. In addition, interdisciplinarity between orthodontics and oral and maxillofacial surgery is essential for careful planning of extraction, making it possible to avoid root resorption and iatrogenesis, in addition to restoring function and aesthetics of the dental arch.